Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1089/neu.2011.1841
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-Induced Plasmalemma Disruptions in Three-Dimensional Neural Cultures Are Dependent on Strain Modality and Rate

Abstract: Traumatic brain injury (TBI) results from cell dysfunction or death following supra-threshold physical loading. Neural plasmalemma compromise has been observed following traumatic neural insults; however, the biomechanical thresholds and time-course of such disruptions remain poorly understood. In order to investigate trauma-induced membrane disruptions, we induced dynamic strain fields (0.50 shear or compressive strain at 1, 10, or 30?sec(?1) strain rate) in 3-D neuronal-astrocytic co-cultures (>500??m thick)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 62 publications
(70 reference statements)
3
91
1
Order By: Relevance
“…The intensity and duration of the mechanical force exerted on the cell is positively correlated to the degree of mechanoporation and the influx of calcium (Lusardi et al, 2004b). Despite this influx of calcium, mechanoporated neurons have been shown, both within this report and by others, to maintain the potential for repair and membrane resealing (Geddes et al, 2003a;Farkas et al, 2006;Whalen et al, 2008;Cullen et al, 2011). In the current study, a subset of neurons showing mechanoporation at the initiation of injury underwent membrane resealing, while the neurons that had sustained more chronic membrane poration appear to undergo pathological change that is in agreement with both in-vitro and in-vivo studies that show a subset of the membrane porated neurons proceeding to cell death (Geddes et al, 2003b;Lusardi et al, 2004b).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The intensity and duration of the mechanical force exerted on the cell is positively correlated to the degree of mechanoporation and the influx of calcium (Lusardi et al, 2004b). Despite this influx of calcium, mechanoporated neurons have been shown, both within this report and by others, to maintain the potential for repair and membrane resealing (Geddes et al, 2003a;Farkas et al, 2006;Whalen et al, 2008;Cullen et al, 2011). In the current study, a subset of neurons showing mechanoporation at the initiation of injury underwent membrane resealing, while the neurons that had sustained more chronic membrane poration appear to undergo pathological change that is in agreement with both in-vitro and in-vivo studies that show a subset of the membrane porated neurons proceeding to cell death (Geddes et al, 2003b;Lusardi et al, 2004b).…”
Section: Discussionsupporting
confidence: 48%
“…This membrane poration can be initiated at the onset of injury and precipitated at more chronic time points after injury (Singleton and Povlishock, 2004;Farkas et al, 2006;Cullen et al, 2011). Our data show that elevated ICP after TBI affects various neuronal pathologies in different ways.…”
Section: Discussionmentioning
confidence: 72%
“…The strain-rate dependence of cell injury has been observed in 3D matrix cultured neurons and astrocytes, showing an increase in membrane permeability to small molecules and an increase in post-insult cell death. 24,29 However, this effect was not observed in hippocampal tissues under biaxial stretch at strain rates ranging from 0.1 to 50 s -1 , 33 and we have showed that dye leakage in stretched dystrophic myocytes could be inhibited by GsMTx4, suggesting that the membrane breakdown was secondary to the applied stress. 48 Different cell types have different properties, which is not surprising.…”
Section: Discussionmentioning
confidence: 79%
“…23 Further, traumatic cell injury depends not only on the intensity of the loading, but also on the loading rate. 24,25 Rapid shear deformations increase the membrane permeability to small dye molecules and also decrease cell viability. 24 These studies suggest that cascades of cell responses are governed by multiple parameters.…”
Section: Introductionmentioning
confidence: 99%
“…This relates to recent observations that demonstrate how neuronal networks that appear structurally undamaged can still contribute to functional impairment because of their aberrant intracellular or intercellular signaling. 13,14 Several neuroimaging methods have been applied to study brain function in patients with TBI, including positron emission tomography (PET), 15 cerebral blood flow (CBF), 9 cerebral blood volume (CBV), 16 and functional magnetic resonance imaging (fMRI). [17][18][19] The major limitation in patient studies relates to the lack of histological verification of imaging findings.…”
Section: Introductionmentioning
confidence: 99%